Tooth-Supported Overdenture Retained with Ball Attachments and Custom-made Coping: A Case Report - Singh, Sandeep; Rathee, Manu; Ghalaut, Pankaj; Malik, Sanju; Wakure, Poonam (Indonesian Dental Association, 2022)
Introduction: Tooth-supported overdentures is a simple and cost-efficient modality that helps preserve bone. This concept is completely supported by DeVan’s maxim: “Perpetual preservation of what is left is more important than the exact replacement of what is lost.” The preserved tooth structure beneath the denture base prevents alveolar ridge resorption, enhances proprioception, and improves denture support and stability. Additionally, using copings on the remaining teeth improves the denture’s retention. Case Report: A 49-year-old female patient reported having the chief complaint of difficulty in chewing food due to missing teeth in the upper and lower arch. An intraoral examination revealed a partially edentulous maxillary arch with denture-induced stomatitis as the patient had a faulty maxillary removable partial denture for five years. The mandibular arch was also partially edentulous, and only mandibular left second premolar and right first and second premolar were present. The patient was advised to stop using maxillary removable partial denture (RPD) altogether and was given an antifungal tablet as well as a multivitamin tab and topical clotrimazole. This case report describes prosthodontic rehabilitation of a mandibular’s partially edentulous arch with tooth-supported overdenture using ball attachments and custom-made coping. Conclusion: For edentulous patients with few remaining teeth, a mandibular tooth-supported overdenture is one of the best and most practical, feasible, and comfortable treatment alternatives. The patient was satisfied with the treatment outcome.